SOCIAL MEDIA AS A TOOL FOR LEARNING ENGLISH TO MOTIVATE LEARNING ACTIVITIES IN STUDENTS OF INFORMATION AND COMPUTER TECHNOLOGY FACULTIES Case study: Institut Bakti Nusantara - Waziana, Winia; Suningsih, Sri (JLCEdu (Journal of Learning and Character Education), 2023)
English has been introduced and studied from an early age till University because it is still introductory, so students are certainly not proficient in communicating with that language. The problem raised in this study is why is the level of student's English proficiency in FTIKOM semester 2 IBN 2022/2023 academic year low? How to increase student motivation in learning English? And what learning strategies can influence student learning motivation in English courses? In this study, researchers used a descriptive method with a qualitative approach. The conclusions in this study are (1) The low level of understanding and learning motivation of FTIKOM students in semester 2 of IBN for the 2022/2023 academic year is caused by first, English is not a favorite subject. Second, the effect of the Covid 19 pandemic which requires students to study at home, and only online. Online learning in district areas cannot be implemented optimally. Therefore, high school graduates who currently occupy lecture seats in semester 2 have low English skills and lack motivation to study. (2) In this study it was found that the use of YouTube social media can increase the learning motivation of FTIKOM faculty students in semester 2 of IBN for the 2022-2023 academic year. (3) Learning strategies using YouTube social media can affect student learning motivation in English courses because learning content from YouTube has a relatively long duration of explanation compared to English learning content on other social media, as well as students can replay the learning video to understand the material.